Continuous and symmetric trans-capacitance compact model for triple-gate junctionless MOSFETs. (January 2021) - Oproglidis, T.A.; Tsormpatzoglou, A.; Tassis, D.H.; Theodorou, C.G.; Ghibaudo, G.; Dimitriadis, C.A.
Highlights: Trans-capacitance compact model for triple-gate junctionless MOSFETs. Validation of the trans -capacitance compact model with TCAD simulations. AC symmetry tests of the trans -capacitance compact model. Abstract: In this work, a continuous and symmetric trans -capacitance compact model for triple-gate junctionless MOSFETs is presented, valid in all regions of operation. Initially, the expressions of the gate, drain and source total charges are analytically derived based on a continuous and symmetric drain current compact model already developed. Then, the intrinsic capacitances are calculated via the differentiation of the terminal charges, verified against TCAD simulation data. The AC symmetry tests of the trans -capacitance compact model are thoroughly investigated.